Implementation of two fuzzy-based systems for IoT device selection in opportunistic networks: effect of storage parameter on IoT device selection. (2018) - Cuka, Miralda; Elmazi, Donald; Kulla, Elis; Oda, Tetsuya; Ikeda, Makoto; Barolli, Leonard
Recently, there are many research works on opportunistic networks and internet of things (IoT). In this paper, we integrate these two technologies by using fuzzy logic. We propose a fuzzy-based approach and implement two fuzzy-based systems for IoT device selection in opportunistic networks. We call the implemented systems: FSIO1 and FSIO2. For FSIO1, we use three input parameters: IoT device speed (IDS), IoT device distance from task (IDDT) and IoT device remaining energy (IDRE). The output parameter is IoT device selection decision (IDSD). For FSIO2, we consider four input parameters by adding IoT device storage (IDST) as a new parameter. Comparing complexity of FSIO1 and FSIO2, the FSIO2 is more complex than FSIO1. But, the FSIO2 is more flexible and makes a better selection of IoT devices than FSIO1.